Spontaneous pneumopericardium, pneumomediastinum and subcutaneous emphysema: unusual complications of asthma in a 2-year-old boy. Issue 6 (19th May 2006) - Ameh, V; Jenner, R; Jilani, N; Bradbury, A
Abstract : A 2-year-old boy presented to the emergency department with a history of sudden onset of cough, dyspnoea and a slight expiratory wheeze on the right lung base. He also had subcutaneous emphysema on the left side of the chest anteriorly. Chest x ray confirmed subcutaneous emphysema and also revealed pneumomediastinum and pneumopericardium. He had had no previous episode and was not known to have asthma. He was apyrexial but had a raised white cell count. The eosinophil count was within normal limits. He was successfully treated with nebulised salbutamol, steroids, antibiotics and high flow oxygen. He made a good recovery and was discharged after 7 days. This case highlights the need for a high index of suspicion of asthma in very young children presenting for the first time with such complications.